2020
DOI: 10.1111/jdv.16726
|View full text |Cite
|
Sign up to set email alerts
|

Sexual impairment in patients with hidradenitis suppurativa: a systematic review

Abstract: Hidradenitis suppurativa (HS) can cause considerable impact on several aspects of quality of life. Sexuality is a central aspect of quality of life. In recent years, there has been an increase in the number of articles on HS and sexuality. To achieve our aim of synthesizing the available scientific evidence on HS and sexual health, we conducted a systematic review in February 2020. The clinical databases used included Medline and Embase. All types of epidemiological articles were included; reviews, guidelines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 48 publications
5
33
1
1
Order By: Relevance
“…The higher number of draining tunnels in women with fulfilled reproductive desires is explained by their longer disease duration and their more severe disease. Although we did not find differences between affected areas in two groups, the involvement of the genitalia area might influence pregnancy desires, in agreement with higher psychological impact on these patients [55].…”
Section: Discussionsupporting
confidence: 82%
“…The higher number of draining tunnels in women with fulfilled reproductive desires is explained by their longer disease duration and their more severe disease. Although we did not find differences between affected areas in two groups, the involvement of the genitalia area might influence pregnancy desires, in agreement with higher psychological impact on these patients [55].…”
Section: Discussionsupporting
confidence: 82%
“…21 The most recent systematic review about HS and sexuality has observed important sexual distress (SD) in patients with HS, some factors related to SD were: female gender, the presence of active lesions in the groin and genital areas, the intensity of pain and unpleasant odour. 22 In our study, however, no differences were observed in both groups in relation to the DLQI score. This result can be explained given that it only included women, baseline Hurley score in both groups was already high and that QoL was equally affected, probably because these patients belonged to a hospital cohort with a severe disease.…”
Section: Discussioncontrasting
confidence: 68%
“…Impairment of QoL was associated with anogenital involvement, early onset of HS, disease severity and activity 21 . The most recent systematic review about HS and sexuality has observed important sexual distress (SD) in patients with HS, some factors related to SD were: female gender, the presence of active lesions in the groin and genital areas, the intensity of pain and unpleasant odour 22 . In our study, however, no differences were observed in both groups in relation to the DLQI score.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HS impairs patients' mental health. It has been related to higher levels of depression, anxiety, worse quality of life, sexual dysfunction and a higher suicide risk [44][45][46][47]. HS also has consequences on social relationships and professional careers, as high rates of absenteeism and unemployment have been reported in HS patients [43].…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%